2010
DOI: 10.1111/j.1567-1364.2010.00661.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic interactions among the Arl1 GTPase and intracellular Na+/H+ antiporters in pH homeostasis and cation detoxification

Abstract: The roles of intracellular GTPase Arl1 and organellar cation/H(+) antiporters (Kha1 and Nhx1) in Saccharomyces cerevisiae tolerance to various stress factors were investigated and interesting new phenotypes of strains devoid of these proteins were found. The role of Arl1 GTPase in their tolerance to various cations is not caused by an altered plasma-membrane potential. Besides the known sensitivity of arl1 mutants to high temperature, we discovered their sensitivity to low temperature. We found for the first t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…Arl1 is highly conserved in all eukaryotes with 65% homology to human ADP-ribosylation factor-like protein 1 (Arl1). Arl1 has been shown to be associated with the trans -Golgi and is thought to be required for endosome-Golgi trafficking [45,46]. Arl1- GTP recruits specific receptor proteins to the membrane surface by binding to their GRIP domains, although in yeast, no specific Arl1 binding receptor proteins have yet been identified [44,45].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Arl1 is highly conserved in all eukaryotes with 65% homology to human ADP-ribosylation factor-like protein 1 (Arl1). Arl1 has been shown to be associated with the trans -Golgi and is thought to be required for endosome-Golgi trafficking [45,46]. Arl1- GTP recruits specific receptor proteins to the membrane surface by binding to their GRIP domains, although in yeast, no specific Arl1 binding receptor proteins have yet been identified [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Arl1- GTP recruits specific receptor proteins to the membrane surface by binding to their GRIP domains, although in yeast, no specific Arl1 binding receptor proteins have yet been identified [44,45]. Mutations in yeast ARL1 are not lethal [28] but ARL1 mutants do show mild defects in localizing proteins to vacuoles as well as defects in potassium uptake [44,46-48]. arl1 mutants have also been shown to be more sensitive to antifungal agents such as Hygromycin B [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High temperature could result in an increase in membrane permeability, allowing for greater diffusion of Na + , H + and K + , thus disturbing the internal pH homeostasis (Coote et al, 1991;Konings et al, 2002). In S. cerevisiae, two antiporters involved in K + efflux have been reported to participate in the detoxification and/or cell response to various extracellular stress, including non-optimal temperatures (Marešová and Sychrová, 2010). Moreover, in mammalian cells, it has been reported that there is a linear relationship between thermosensitivity and internal pH, which could be mediated by a Na + /H + antiporter (Liu et al, 1996a;Liu et al, 1996b).…”
Section: Discussionmentioning
confidence: 99%
“…Growth of Saccharomyces cerevisiae at sub-lethal temperature revealed increasing activity of membrane ATPase, which is responsible for intracellular pH homeostasis (Coote et al, 1991). In addition, the intracellular GTPase Arl1 and organellar cation/H + antiporters (Kha1 and Nhx1) of S. cerevisiae were found to be important for survival at nonoptimal pH, temperature and cation concentration (Marešová and Sychrová, 2010). Such perturbations Abbreviations: AAB, acetic acid bacteria; AO, acridine orange; ISO, inside-out; YPG, yeast extract-peptone-glycerol.…”
Section: Introductionmentioning
confidence: 99%